The decline of the conquerors: the limits of wealth and loyalty during the rebellion of the encomenderos in the viceroyalty of Peru, 1544-1548 - Escudero Villanueva, Alfredo Luis (2019)
The defeat of the encomenderos’ rebellion (1544-1548), led in the viceroyalty of Peru by Gonzalo Pizarro against the Spaniard crown is described, emphasizing its failure due to the economic stagnation in that period. At the beginning of the rebellion, Gonzalo Pizarro was able to establish control over the territory and its resources. However, the decrease of indigenous labor and the encomienda’s production added to the annoyance of neighbors and encomenderos caused by the negative impact of the war and undermined Pizarro’s authority and the rebel movement.